Karakterisasi dan Optimasi penggunaan Katalis CaO/SiO₂ dari Biomassa untuk Sintesis Biodiesel dari Minyak Jelantah - Dian, Amalia; Meka Saima Perdani; Hilman Imadul Umam; Christin Octaviani Sitanggang; Eti Ayu Nurhana (P3M Politeknik Negeri Jember, 2025)
Environmentally friendly biodiesel can be produced from used cooking oil through transesterification with heterogeneous catalysts. This study synthesized CaO–SiO₂ catalysts from eggshells and rice husks through calcination and impregnation, with a reaction at 65°C, an oil:methanol ratio of 1:9, and a catalyst variation of 4–8%. FTIR, SEM, and BET characterizations showed the presence of CaO and Si–O–Si with porous morphology and surface area that support catalytic activity. The best results were achieved at 4% catalyst with a conversion of 63.64%, demonstrating the potential of biomass as a sustainable catalyst for biodiesel production.